Adenoid cystic carcinoma of the breast with distant metastasis to the liver and spleen: a case report - Gillie, Breanne (J Surg Case Rep, 2020)
Adenoid cystic carcinoma (ACC) of the breast is a rare malignancy, accounting for 0.1–1% of breast cancers. Histologically breast ACC is similar to ACC’s found in salivary tissue and is a triple-negative breast cancer with an uncharacteristically favorable prognosis and low incidence of metastasis. Most cases present as a painful, palpable mass; however, asymptomatic cases found on screening mammograms have also been noted. Core needle biopsy or excisional biopsy is necessary for definitive diagnosis of breast ACC. Immunohistochemistry of these cancers can differentiate breast ACC from masses with similar histology, such as invasive cribriform carcinoma and collagenous spherulosis. There is no well-established treatment guideline for ACC; however, it has been noted that reoccurrence and metastasis are noted more in cases of local resection than mastectomy.